دور الإعلام السلبي في تفشي ظاهرة الحرب من منظور الفقه الإسلامي والقانون الدولي - Shaddad, Mohammed Ahmed Qasem; Buang, Ahmad Hidayat (Jurnal Fiqh, 2016)
This article aims at examining the importance of media and its negative role in the spread of war and its impact on people from the perspectives of Islamic jurisprudence and international law. This is because media has become one of the most important tool of psychological warfare propaganda to influence peoplesÂ’ beliefs and behaviors. In order to achieve the objectives of the study, the comparative analytical inductive method of the religious and legal texts and historic events of wars were used. The results of the study reveal that governments and political regimes have established media organizations that control the public opinion of the masses to manipulate peopleÂ’s perspective and persuading them on the justification of their wars. They utilize the media in a manipulative manner in order to misguide people, to disfigure their ideas, and to confiscate the right of people to live in peace. Also, the study found out that journalists have been subject to risk and violations during the coverage of wars due to the nature of their jobs. Despite the protection of the international and Islamic laws, none of the perpetrators were brought to justice.